Analysis of diabetes mellitus and environmental tobacco exposure of smoke (ETS) as a lung's tuberculosis risk factor - Mariana Mariana; Emma Novita; Agita Dior; Zatah Ismah; Gresi Elyantari; Aulia Hayyu Ravenia (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2018)
Indonesia is the country with the second highest pulmonary TB case in the world. Some studies suggest there is a relationship between TB and diabetes. Smoking habits are also associated because it can damage the defense mechanism of the lungs so as to facilitate the entry of TB germs. This study was conducted to analyze diabetes mellitus and environmental exposure to tobacco smoke ( ETS) as a risk factor for pulmonary tuberculosis. Thisresearch is a quantitative analytical research with Case-Control performed in TB endemic region in Palembang namely Puskesmas Kertapati, health centers and health centers Sei Selincah 23 Ilir February to May 2018. Data were obtained from primary data obtained from questionnaires and examinations physic-cal. The statistical test used is the Chi-square test and Independent T-test. In this study showed a significant relationshipbetween bloodsugar levels with tuberculosis status (p = 0.000 ).And there is a significant relationship between ETS with tuberculosis status.